Teaching Practices in the 21st Century in Kenya: A Qualitative Approach - Kaume-Mwinzi, Regina K. (International Journal of Educational Excellence, 2018)
Education is an engine for the growth and progress of any society and it is responsible for building human capital which sets technological and economic growth. In the pre-technology education context, the teacher controlled the instructional process, the content was delivered to the entire class and the teacher emphasized factual knowledge. However, the current global demands in education require the use of approaches that are learner-centered and embracing integration of ICT. The purpose of this study is to establish the pedagogy used in Kenya for the 21st century learner. The case study design was used to collect qualitative data from three teachers who were purposively sampled from three education sub-sectors in Kenya: primary, secondary and university. The interview was guided by three research questions: Which teaching practices are used in Kenya? Which are the ‘best’ teaching practices in Kenya in the 21st century? What are the barriers for the ‘best’ teaching practices in Kenya? The findings were that the teaching methods currently in use were mainly teacher-centered although the respondents revealed that the ‘best’ teaching practices for the 21st century learner were student-centered. However, the barriers were large classes, lack of resources and facilities among other factors. The study recommends realignment of education policies to give priority to build pedagogical capabilities of teachers, provide digital tools and other resources. This would enable the 21st century learners’ opportunity to unleash their potential.

Scaling up successfully: Lessons from Kenya’s Tusome national literacy program - Piper, Benjamin; Destefano, Joseph; Kinyanjui, Esther M.; Ong’ele, Salome (Journal of Educational Change, 2018)
Many successful piloted programs fail when scaled up to a national level. In Kenya, which has a long history of particularly ineffective implementation after successful pilot programs, the Tusome national literacy program—which receives funding from the United States Agency for International Development—is a national-level scale-up of previous literacy and numeracy programs. We applied a scaling framework (Crouch and DeStefano in Doing reform differently: combining rigor and practicality in implementation and evaluation of system reforms. International development group working paper no. 2017-01, RTI International, Research Triangle Park, NC, 2017. https://www.rti.org/publication/doing-reform-differently-combining-rigor-and-practicality-implementation-and-evaluation) to examine whether Tusome’s implementation was rolled out in ways that would enable government structures and officers to respond effectively to the new program. We found that Tusome was able to clarify expectations for implementation and outcomes nationally using benchmarks for Kiswahili and English learning outcomes, and that these expectations were communicated all the way down to the school level. We noted that the essential program inputs were provided fairly consistently, across the nation. In addition, our analyses showed that Kenya developed functional, if simple, accountability and feedback mechanisms to track performance against benchmark expectations. We also established that the Tusome feedback data were utilized to encourage greater levels of instructional support within Kenya’s county level structures for education quality support. The results indicated that several of the key elements for successful scale-up were therefore put in place. However, we also discovered that Tusome failed to fully exploit the available classroom observational data to better target instructional support. In the context of this scaling framework, the Tusome literacy program’s external evaluation results showed program impacts of 0.6–1.0 standard deviations on English and Kiswahili learning outcomes. The program implemented a functional classroom observational feedback system through existing government systems, although usage of those systems varied widely across Kenya. Classroom visits, even if still falling short of the desired rate, were far more frequent, were focused on instructional quality, and included basic feedback and advice to teachers. These findings are promising with respect to the ability of countries facing quality problems to implement a coherent instructional reform through government systems at scale.
Keywords: ___working_potential_duplicate

National Education Sector Strategic Plan - Ministry of Education, Kenya (2018)

National Education Sector Strategic Plan v2 - Ministry of Education, Kenya (2018)

National Pre-primary Education Policy Standard Guidelines - Republic of Kenya Ministry of Education (Republic of Kenya Ministry of Education, 2018)

Kenya National Education Sector Strategic Plan 2018 - 2022 - Ministry of Education, Republic of Kenya (2018)

Kenya National Examination Council (2018)

GPE 2020 Country-level Prospective Evaluations: First annual Report Kenya - Rawal, Prepared Shenila; Aslam, Monazza; Outhred, Rachel (2018)
Keywords: ⛔ No DOI found

Examining the secondary effects of mother-tongue literacy instruction in Kenya: Impacts on student learning in English, Kiswahili, and mathematics - Piper, Benjamin; Zuilkowski, Stephanie Simmons; Kwayumba, Dunston; Oyanga, Arbogast (International Journal of Educational Development, 2018)

M-Shule - Together we learn, together we succeed - M-Schule LTd (2018)
M-Shule is the first adaptive, mobile learning management platform designed to improve performance for millions of primary school students across Kenya and Sub-Saharan Africa

A second chance to dream: initiating ODeL in secondary school re-entry programs for young adult secondary school dropouts the case of Mumias District, Western Kenya - Musita, Richard; Ogange, Betty O.; Lugendo, Dorine (Distance Education, 2018)
The Kenyan education system has very limited re-entry options for learners who drop out before attaining secondary school certificate. It is very difficult to access training and or secure a job that requires at least secondary school education. This study examined the prospects of initiating Open and Distance e-Learning(ODeL) in re-entry programmes into high school for out of school Young Adult Secondary School Dropouts (Y.A.S.S.D). The study focused on the enablers and challenges of initiating ODeL in the secondary school re-entry programmes. An alternative flexible and sustainable community based ODeL model that potentially can address re-entry for the Y.A.S.S.D is proposed. A qualitative phenomenological design was used; focus group discussion and interviews were conducted from a purposeful sample of participants. The study revealed that the potential of ODeL in addressing re-entry into secondary school for Y.A.S.S.D great. Majority of the participants were aware of the existing secondary school re-entry options, however, ODeL appeared new. Despite there being challenges in introducing the ODeL mode of study in secondary school re-entry programmes, it is viable and requires further exploration. The enablers of this mode of study are largely in place to the extent appreciated by participants in the study.
Keywords: Re-entry; dropouts; open distance e-learning

Experimental evidence on scaling up education reforms in Kenya - Bold, Tessa; Kimenyi, Mwangi; Mwabu, Germano; Ng’ang’a, Alice; Sandefur, Justin (Journal of Public Economics, 2018)
What constraints arise when translating successful NGO programs to improve public services in developing countries into government policy? We report on a randomized trial embedded within a nationwide reform of teacher hiring in Kenyan government primary schools. New teachers offered a fixed-term contract by an international NGO significantly raised student test scores, while teachers offered identical contracts by the Kenyan government produced zero impact. Observable differences in teacher characteristics explain little of this gap. Instead, data suggests that bureaucratic and political opposition to the contract reform led to implementation delays and a differential interpretation of identical contract terms. Additionally, contract features that produced larger learning gains in both the NGO and government treatment arms were not adopted by the government outside of the experimental sample.
Keywords: Contract teachers; Education; External validity; Kenya; Randomized evaluation; State capacity

PARENTAL INVOLVEMENT IN PRIMARY SCHOOLS IN KENYA AS A MAJOR STRATEGY FOR ACADEMIC SUCCESS - Muigai, Jecinta W. (European Journal of Education Studies, 2018)
The new Kenyan curriculum emphasizes the role of parents as essential to their children’s education and in the success of curriculum implementation. The development requires a change in how parents and the community interact with schools and education. The perception in Kenya has always been that education is the sole responsibility of the school and the teacher. And so, parental involvement in Kenya has mainly been limited to financial contributions and teacher-parent meetings. With the introduction of new curriculum, the role of parent is crucial for the academic success of the child. A literature study investigated the extent of parental involvement in primary schools in Kenya. The data is obtained from a variety of library articles addressing parental involvement in Primary schools in different counties in Kenya. The current study found that majority of parents are involved in their children’s education, however, more awareness of the parental involvement is needed and more strategies on parental involvement needs to be employed for the success of the new curriculum.  Article visualizations:
Keywords: academic achievement; parental involvement; primary schools; ⚠️ Invalid DOI

PARENTAL INVOLVEMENT IN PRIMARY SCHOOLS IN KENYA AS A MAJOR STRATEGY FOR ACADEMIC SUCCESS - Muigai, Jecinta W. (European Journal of Education Studies, 2018)
The new Kenyan curriculum emphasizes the role of parents as essential to their children’s education and in the success of curriculum implementation. The development requires a change in how parents and the community interact with schools and education. The perception in Kenya has always been that education is the sole responsibility of the school and the teacher. And so, parental involvement in Kenya has mainly been limited to financial contributions and teacher-parent meetings. With the introduction of new curriculum, the role of parent is crucial for the academic success of the child. A literature study investigated the extent of parental involvement in primary schools in Kenya. The data is obtained from a variety of library articles addressing parental involvement in Primary schools in different counties in Kenya. The current study found that majority of parents are involved in their children’s education, however, more awareness of the parental involvement is needed and more strategies on parental involvement needs to be employed for the success of the new curriculum.  Article visualizations:
Keywords: academic achievement; parental involvement; primary schools; ⚠️ Invalid DOI

Factors Affecting Adoption of E-Learning Technology in Kenya - Kingori, Rhoda Mbithe (United States International University - Africa, 2018)
Internet penetration in Africa has been accelerated, with Kenya at the fore front at over 89.5% penetration, this penetration has led to an increase in knowledge repository for Kenyans to choose from and as a result E-learning has steadily increased not only in tertiary institutions but in informal learning as well. Facebook and YouTube are some of the web based tools, – that are listed as having potential applications for teaching and learning. As a result, it is essential to understand the challenges faced in the adoption of e-learning technology. The overall purpose of this study was to investigate the factors affecting adoption of e-learning technology in Kenya with a focus on three key factors, self-efficacy, objective usability and system accessibility. This study used explanatory/hypothesis research design to investigate the factors which affect adoption of e-learning technology in Kenya. An explanatory research design was fit to the study because it will helped to ascertain not only the relationship between the different variables, but measure the effect and strength of each independent variable on the dependent variable which was the technology adoption. The target population was social media (Facebook) users in Kenya. According to Internet World Statistics there are over 6.2 million Facebook subscribers in Kenya as of June 2017. This study focused on 200 social media users in Nairobi who were interested in e-learning or have ever learned online. They were sampled by geographic cluster, simple random sampling technique with a focus on Nairobi. Online questionnaire was used by Google form and 93% responded. In the first objective of self-efficacy, the correlation result revealed positive correlation between perceived ease of use with self-efficacy (r=0.441, p<0.05) and perceived usefulness with self-efficacy(r=0.337, p<0.05). On the CFA, there was a strong model equation but on the SEM it was not. The path coefficient for the relationship between SE and adoption of e-learning was weak. In the second objective, the correlation result revealed positive correlation between perceived ease of use with objective usability (r=0.598, p<0.05) and perceived usefulness with SE (r=0.456, p<0.05). Based on SEM, the path coefficient for the relationship between objective usability and adoption of e-learning was significant. Without any latent/intervening variable, OU and PEOU was positive and significant at the 0.05 level (βeta=0.938, T-value =3.658, p<0.05). The positive relationship indicates that one unit increase in OU will result in 0.938 increases in PEOU. In the last objective of system accessibility, the correlation result revealed positive correlation between perceived ease of use with system accessibility (r=0.441, p<0.503) and perceived usefulness with system accessibility (r=0.514, p<0.05). The path coefficient for the relationship between system accessibility and adoption of e-learning was weak and not significant hence dropped from the model.The research established that Self-efficacy had little to no effect on adoption of e-learning technology in Kenya. Objective usability was the strongest factor affecting the adoption of e-learning technology while system accessibility had correlation but was not strong enough to impact the model and as such impact the adoption of e-learning technology in Kenya was weak. These findings provided some useful insights for governments, potential instructors or educators, e-learning platforms and policy makers. This recommends and highlights the need to shift from the metropolitan areas to the rural areas in order to get a holistic view of the e-learning environment in Kenya. This research shed light on objective usability as a strong factor on perceived ease of use and perceived usefulness and as such on the adoption of e-learning technology in Kenya. Based the responses received and the SEM analysis further research should focus on the two variables of system accessibility and self-efficacy involving a larger number of variables to examine, as well as larger numbers of respondents to support the factor analysis. Research should also focus on attitude and behavioral intention and their interaction with perceived eases of use and perceived usefulness. The research needs to now shift from the metropolitan areas to the rural areas in order to get a holistic view of the e-learning environment in Kenya.

Scaling up successfully: Lessons from Kenya’s Tusome national literacy program - Piper, Benjamin; Destefano, Joseph; Kinyanjui, Esther M.; Ong’ele, Salome (Journal of Educational Change, 2018)
Many successful piloted programs fail when scaled up to a national level. In Kenya, which has a long history of particularly ineffective implementation after successful pilot programs, the Tusome national literacy program—which receives funding from the United States Agency for International Development—is a national-level scale-up of previous literacy and numeracy programs. We applied a scaling framework (Crouch and DeStefano in Doing reform differently: combining rigor and practicality in implementation and evaluation of system reforms. International development group working paper no. 2017-01, RTI International, Research Triangle Park, NC, 2017. https://www.rti.org/publication/doing-reform-differently-combining-rigor-and-practicality-implementation-and-evaluation) to examine whether Tusome’s implementation was rolled out in ways that would enable government structures and officers to respond effectively to the new program. We found that Tusome was able to clarify expectations for implementation and outcomes nationally using benchmarks for Kiswahili and English learning outcomes, and that these expectations were communicated all the way down to the school level. We noted that the essential program inputs were provided fairly consistently, across the nation. In addition, our analyses showed that Kenya developed functional, if simple, accountability and feedback mechanisms to track performance against benchmark expectations. We also established that the Tusome feedback data were utilized to encourage greater levels of instructional support within Kenya’s county level structures for education quality support. The results indicated that several of the key elements for successful scale-up were therefore put in place. However, we also discovered that Tusome failed to fully exploit the available classroom observational data to better target instructional support. In the context of this scaling framework, the Tusome literacy program’s external evaluation results showed program impacts of 0.6–1.0 standard deviations on English and Kiswahili learning outcomes. The program implemented a functional classroom observational feedback system through existing government systems, although usage of those systems varied widely across Kenya. Classroom visits, even if still falling short of the desired rate, were far more frequent, were focused on instructional quality, and included basic feedback and advice to teachers. These findings are promising with respect to the ability of countries facing quality problems to implement a coherent instructional reform through government systems at scale.
Keywords: ___working_potential_duplicate

Scaling up successfully: Lessons from Kenya’s Tusome national literacy program - Piper, Benjamin; Destefano, Joseph; Kinyanjui, Esther M.; Ong’ele, Salome (Journal of Educational Change, 2018)
Many successful piloted programs fail when scaled up to a national level. In Kenya, which has a long history of particularly ineffective implementation after successful pilot programs, the Tusome national literacy program—which receives funding from the United States Agency for International Development—is a national-level scale-up of previous literacy and numeracy programs. We applied a scaling framework (Crouch and DeStefano in Doing reform differently: combining rigor and practicality in implementation and evaluation of system reforms. International development group working paper no. 2017-01, RTI International, Research Triangle Park, NC, 2017. https://www.rti.org/publication/doing-reform-differently-combining-rigor-and-practicality-implementation-and-evaluation) to examine whether Tusome’s implementation was rolled out in ways that would enable government structures and officers to respond effectively to the new program. We found that Tusome was able to clarify expectations for implementation and outcomes nationally using benchmarks for Kiswahili and English learning outcomes, and that these expectations were communicated all the way down to the school level. We noted that the essential program inputs were provided fairly consistently, across the nation. In addition, our analyses showed that Kenya developed functional, if simple, accountability and feedback mechanisms to track performance against benchmark expectations. We also established that the Tusome feedback data were utilized to encourage greater levels of instructional support within Kenya’s county level structures for education quality support. The results indicated that several of the key elements for successful scale-up were therefore put in place. However, we also discovered that Tusome failed to fully exploit the available classroom observational data to better target instructional support. In the context of this scaling framework, the Tusome literacy program’s external evaluation results showed program impacts of 0.6–1.0 standard deviations on English and Kiswahili learning outcomes. The program implemented a functional classroom observational feedback system through existing government systems, although usage of those systems varied widely across Kenya. Classroom visits, even if still falling short of the desired rate, were far more frequent, were focused on instructional quality, and included basic feedback and advice to teachers. These findings are promising with respect to the ability of countries facing quality problems to implement a coherent instructional reform through government systems at scale.
Keywords: Evaluation; Implementation; Literacy; National; Reading; Reform; Systems

Reward management strategies on employee performance in selected universities in Nakuru County, Kenya - Kathombe, Mary Wambui (Egerton University, 2018)
Rewards play an important role in increasing employee job satisfaction resulting in improving organizational performance. Motivated employees are the cornerstone of any successful organization. The main objective of this study was to establish the effects of reward management strategies on employee performance in selected universities in Nakuru County. The specific objectives were: to determine the effect of financial rewards on employee performance, to determine the effect of non-financial rewards on employee performance and to determine the combined effect of financial and non-financial rewards on employee performance. Descriptive survey design was adopted in conducting this study, as it was suitable for collecting information that described an existing phenomenon. The target population was 620 lecturers in two universities in Kenya namely Egerton and Kabarak Universities, which comprised a sample of 242 lecturers. The study primarily used a questionnaire to gather data from the respondents. Data from the questionnaire were systematically analyzed according to the research objectives and hypotheses. All hypotheses were tested using regression statistics and the results of the findings established that there is a strong positive association between combined effect of financial and non-financial rewards on employees‟ performance. According to the findings of this study, financial and non-financial rewards motivate employees to better performance. Thus, employee performance will be high in Kenyan universities that adopt an integrated effort on both financial and non-financial reward measurements. The study recommends the following: First, lecturers‟ promotion should be done regularly on merit. Secondly, Universities establish a competitive retirement benefit scheme to its employees. Third, Universities should engage their lecturers on regular training programs.

The Role of Language in the Teaching and Learning of Early Grade Mathematics: An 11-year Account of Research in Kenya, Malawi and South Africa - Essien, Anthony (African Journal of Research in Mathematics, Science and Technology Education, 2018)
The purpose of this study was to provide a systematic review of research that has been carried out between 2006 and 2016 on the role of language in early grade (Grades 1–4) mathematics teaching and learning in three countries—Kenya, Malawi and South Africa. These countries were selected because they have similar characteristics: teaching and learning occur in a multilingual context; their language in education policies are similar; transition from mother tongue to English happens during the early grades; and most of the learners learn mathematics in English—a language which for most is not their first/home language. Research outputs between 2006 and 2016 from the three countries were sourced from peer-reviewed mathematics and general education journals, monitoring and evaluation reports, and book chapters. Findings from the study revealed that there is a lack of longitudinal studies that investigate the impact of language on the teaching and learning of mathematics and that there are few studies on how teachers are and should be trained to teach mathematics in the early grades. The study also found that the implementation of the language in education policies in the three different focus countries is fraught with difficulties owing to a number of factors, amongst them the fact that the indigenous languages are not yet fully developed as academic languages. Finally, existing literature highlights the importance of the use of code switching and the provision of materials in the home language(s) of early graders. Recommendations regarding policy/curriculum, teacher education and pedagogic practices are made.

Standards for Competence Based Digital Course Materials - Kenya Institute of Curriculum Development (2018)

Identifying the essential ingredients to literacy and numeracy improvement: Teacher professional development and coaching, student textbooks, and structured teachers’ guides - Piper, Benjamin; Simmons Zuilkowski, Stephanie; Dubeck, Margaret; Jepkemei, Evelyn; King, Simon J. (World Development, 2018)
Several rigorously evaluated programs have recently shown positive effects on early literacy and numeracy outcomes in developing countries. However, these programs have not been designed to evaluate which ingredients of the interventions are most essential to improve literacy outcomes. Policy makers therefore lack evidence as to whether program ingredients such as teacher professional development (PD), instructional coaching, learner materials, teachers’ guides, community support, or technology are required for program impact. The Kenya Primary Math and Reading Initiative was a randomized controlled trial that compared three treatment groups with speciﬁc ingredients and a control group. Using literacy and numeracy outcome measures for grades 1 and 2, we evaluated the beneﬁts of the following ingredients: (1) teacher PD and teacher instructional support and coaching; (2) revised student books in literacy and numeracy, at a 1:1 ratio, added to PD and instructional support; and (3) structured teacher lesson plans added to student books, PD, and instructional support. We found that two of the three combinations of ingredients had statistically signiﬁcant positive impacts on learning outcomes. The results showed that the third combination—PD, teacher instructional support and coaching, 1:1 student books, and structured teacher lesson plans—was most effective. A cost-effectiveness analysis on the ingredients showed that the option of PD and instructional support, 1:1 revised books, and teachers’ guides was the most expensive, but that the additional impact on learning made this the most cost-effective intervention. This study rigorously analyzes which ingredients for literacy and numeracy improvement would be most effective for overall impact, and suggests to policy makers that careful decisions regarding program ingredients will lead to more effectively designed and implemented interventions to improve learning in developing countries.
Keywords: Africa; C:Kenya; Literacy; Numeracy; Program Evaluation; Program evaluation; Quantitative; Randomized controlled trial; Reading; Teacher Professional Development; ___working_potential_duplicate; numeracy; randomized control trial

Assessment of public primary school teachers preparedness in the implementation of digital literacy programme in public primary schools in Imenti north sub-county, Kenya - Nyaga, Felistas (University of Nairobi, 2018)
The purpose of this study was to investigate the preparedness of public primary school teachers in the implementation of digital literacy programme in Imenti North Sub County Kenya. The study was guided by the following objectives; to establish infrastructural availability for the public primary school teachers’ usage in teaching and learning in implementation of digital literacy programme in public primary schools in Imenti North Sub County, to examine how public primary school teachers’ competence influence implementation of digital literacy program in public primary schools in Imenti North Sub County, The study sought to determine how public primary school teacher perception influence implementation of digital literacy program in public primary schools in Imenti North Sub County. The study also sought to establish how digital literacy content availability for the public primary school teachers influence implementation of digital literacy programme in public primary schools in Imenti North Sub County. The study adopted descriptive research design. The study was grounded on technology diffusion theory to explain the relationship between the independent and dependent variables. The study had a target population of 596 respondents who comprised 59 head teachers and 537 teachers. The respondents were selected using proportionate random sampling technique where by a sample size of 137 was used. Primary data was obtained using self-administered questionnaires that were made up of both open ended and closed ended questions, also unstructured interview was administered face-to-face or over the phone. The reliability of the study was measured using test retest method. The Data was analyzed using Statistical Package for Social Sciences and the data was presented in frequency tables, percentages and regression analysis. The study concluded that preparedness of public primary school teachers in the implementation of digital literacy programme was highly influenced by teacher competence followed by infrastructural preparedness and then by Teacher perception while digital literacy content had the least effect on implementation of digital literacy programme in public primary schools in Imenti North Sub County. The study concluded that infrastructural preparedness influences implementation of digital literacy program in public primary schools in Imenti North Sub County significantly. Even though the schools have electricity their computer lab have not been fully equipped. The implementation of digital literacy program has been delayed by inadequate internet connections coupled with inadequate digital literacy program devices for teaching and learning in the schools. Also, there being inadequate tablets for the learners and laptops for the teachers have negatively affected the implementation of digital literacy program in public primary schools. The study recommends that teachers and instructors need to be trained in basic ICT skills and ICT-based teaching methods to feel comfortable about using the materials. The study recommends that the governments should ensure that all the public primary schools are connected to wireless internet services; that primary schools should be assisted by both national and county government need to ensure that the schools have a complete computer lab that is fully equipped with enough laptops for the teachers and tablets for the learners. The study further recommends that head teachers and parents need to set up administrative committees to manage ICT facilities as proven to be very effective in ensuring the sustainability of initiatives.

Third Medium Term Plan 2018-2022 - The National Treasury and Planning (2018)

Impact evaluation of Tayari school readiness program in Kenya - Ngware, Moses; Hungi, Njora; Wekulo, Patricia; Mutisya, Maurice; Njagi, Joan; Muhia, Nelson; Wambiya, Elvis; Donfouet, Hermann; Gathoni, Grace; Mambe, Shem (APHRC, 2018)

Boosting Prosperity, Improving Equity in North and North Eastern Kenya - World Bank (2018)

Teachers’ attitudes towards the utility of computers in education in Kenya - Buliva, Newton (African Educational Research Journal, 2018)

In Bringing a Literacy Project to Scale, has Kenya Found a Holy Grail? - Bruns, Barbara (Center For Global Development, 2018)
An article of faith among development economists is that “evidence-based policy” holds the promise of faster progress. Barbara Bruns set out to find a rigorously evaluated pilot whose evidence had led to a program at scale. It wasn’t easy.

Parental Involvement in Primary Schools in Kenya as a Major Strategy for Academic Success - Muigai, Jecinta W. (European Journal of Education Studies, 2018)
Keywords: ⚠️ Invalid DOI

Mathematics from the beginning: Evaluating the Tayari preprimary program’s impact on early mathematics skills - Piper, Benjamin; Sitabkhan, Yasmin; Nderu, Evangeline (Global Education Review, 2018)
Given the dearth of research on early numeracy interventions in low- and middle-income countries, this paper presents the instructional methodology and impact results of the Tayari program. Tayari is a preprimary intervention in Kenya (2014–2019) that prepares children aged four and five for entry into primary school through materials for students, training for teachers, and continuous in-classroom support. Evidence points to the long-term benefits of developing an early foundation in mathematics. The few preprimary mathematics studies in sub-Saharan Africa have not described the instructional methodology in enough detail to add to our knowledge of best practices. The Tayari methodology was built on the Kenyan government’s preprimary syllabus to produce instruction that was developmentally sequenced, linked to out-of-school experiences, and supportive of children’s number sense. Tayari is evaluated using a randomized controlled trial (RCT) and collection of longitudinal data from 2,957 children in treatment and control schools at three time points. Pupil assessment items were drawn from a growing body of research on preprimary numeracy in developing contexts, plus instruments and techniques from the Measuring Early Learning and Quality Outcomes (MELQO) program (UNESCO, UNICEF, Brookings Institution, & World Bank Group, 2017). The endline impact evaluation of the longitudinal RCT results showed statistically significant effects in the numeracy tasks of producing sets, identifying numbers, and naming shapes, while revealing no initial effects in the areas of oral and mental addition. We present recommendations for Tayari’s improvement in terms of mathematics instruction, as well as preprimary policy implications for Kenya and similar contexts.
Keywords: Sub-Saharan Africa; ⛔ No DOI found

Massive Open Online Courses (MOOCs) for Professional Teacher and Teacher Educator Development: A Case of TESSA MOOC in Kenya - Wambugu, Patriciah W. (Universal Journal of Educational Research, 2018)
This study intends to present a bespoke teacher professional development MOOC designed by Teacher Education for Sub-Saharan Africa (TESSA) team that allows MOOCs to become a viable means offering cost-effective, quality professional teacher development. TESSA is a network of teachers and teacher educators, working to improve classroom teaching in Africa. TESSA MOOC is an innovative approach to capacity building for teacher educators and teachers across Africa. The study presents outputs of an evaluation of TESSA MOOC course undertaken by Kenyan teachers and teacher educators. The experiences of the participants were that the TESSA MOOC was a new but interesting, appealing and flexible course. In addition, the participants were able to learn from one another and what they learnt may impact on their pedagogical skills. Key challenges identified include difficulties in downloading of materials due to lack of internet connectivity and use of ICT phobia for learning. MOOCs represent an untapped potential for teacher professional development that can be a cost and resource effective means to deliver quality education to teachers and teacher educators. Therefore, the teachers and teacher educators may need to exploit this learner based TESSA MOOC to build capacity for teaching.
Keywords: Educational Quality; Faculty Development; Foreign Countries; Information Technology; Online Courses; Teacher Education; Teacher Educators; Teacher Effectiveness

‘Now I want to use it to learn more’: Using mobile phones to further the educational rights of the girl child in Kenya - Zelezny-Green, Ronda (Gender & Development, 2018)
Keywords: Equity through Access; ⛔ No INSPIRE recid found

Teachers as Guides: The role of teachers in the facilitation of technology-mediated learning in an alternative education setting in western Kenya - Radhakrishnan, Dhinesh; DeBoer, Jennifer; Kimani, Samuel (Purdue University, 2018)

UIS Statistics - UNESCO Institute for Statistics (2018)
Keywords: ___working_potential_duplicate

UIS Statistics - UNESCO Institute for Statistics (2018)
Keywords: ___working_potential_duplicate

Support to children’s education in the urban slums of Nairobi: community and parents’ perceptions with an expanded phase of an education intervention program - Abuya, Benta A.; Wekulo, Patricia; Muhia, Nelson (Qualitative Research in Education, 2018)
The objective of this paper is to examine the perceptions of community elders and parents on their roles regarding support to their children’s education. Data come from the qualitative component of a baseline survey conducted in Korogocho and Viwandani, two urban informal settlements in Nairobi, Kenya. Data were collected in April-May 2016 through in-depth interviews, key informant interviews and focus group discussions. Results demonstrated that community elders internalized their role as the face of government in their respective communities, and enforced the implementation of education policies on behalf of all children. The community leaders also saw as part of their role the need to encourage parents to be active participants in their children’s education. Female parents with boys in the program perceived that parental monitoring and follow-up was important to ensure that their children attended school, and completed work assigned by the teachers, more so in Korogocho. Overall, parents recognized the importance of the role they played in their children’s education. This is a good entry point as parental support will ensure the success and sustainability of the intervention to improve educational outcomes for children, which in turn will help their children navigate the challenging period that adolescence presents.
Keywords: teachers

An Investigation into Implementation of ICT in ECD and Primary Schools, in the Light of Free Laptops at Primary One: a case study of teachers implementing ICT into their teaching practice - Tonui, Betty C.; Kerich, E.; Koross, R.; J, K.; Moi, Too (2018)
Information and communication technologies (ICTs) have been touted as being potentially powerful tools that can be used to facilitate the implied educational change and reform. Implementation of ICT in higher education learning environments is a complex task. Teachers and students, but also management, administration and ICT support are affected by and affect the implementation. To facilitate the change processes better the first step is to actually understand what problems and challenges implementation of ICT leads to and how it affects practice. Although classical instructional methods will continue to be used in the teaching-learning process, it is also true that Information Communication Technologies (ICTs) can be harnessed to become powerful pedagogical tools. Proceeding from the premise that there are many ways to use new technologies for teaching and learning, the paper presents literature on the possibilities and challenges of integrating ICT into teaching-learning, the rationale for adopting and using ICTs for learning-teaching, as well as the key factors that influence the adoption and use of ICTs in teaching and learning both from a general perspective and in a technical education context. The paper then outlines and discusses findings of a study designed to investigate the possibilities and challenges of using Information Communication Technology (ICT) in teaching-learning procedures in primary school institutions in Kenya using data obtained from a Tinderet District school in the Rift valley

Technology for Inclusive Education (TFIE) Pilot Report - Digital Literacy Trust (2018)

Gender responsive pedagogy: A toolkit for teachers and schools. 2nd ed. - FAWE (Forum for African Women Educationalists (FAWE)., 2018)

Technology-Supported Professional Development for Teachers: Lessons from Developing Countries - McAleavy, Tony; Hall-Chen, Alex; Horrocks, Sarah; Riggall, Anna (Education Development Trust, 2018)
This report captures what might be learnt from a selection of the world’s most interesting examples of technology-assisted in-service professional development in lower-income countries and from wider reflections about the potential of technology to enhance the professional learning of teachers.
Keywords: Africa; Bangladesh; Blended Learning; C:Low- and middle-income countries; Developing Nations; ERIC, Resources in Education (RIE); Educational Technology; Elementary Education; Elementary School Teachers; Faculty Development; Foreign Countries; Handheld Devices; India; Inservice Teacher Education; Kenya; Large Group Instruction; Nigeria; Online Courses; Pakistan; Policymakers; Practitioners; Refugees; Shared Resources and Services; Social Media; Teaching Methods; Technology Integration; Technology Uses in Education; Telecommunications; ___working_potential_duplicate; ⛔ No DOI found

Sustaining and scaling pedagogic innovation in sub-Saharan Africa: Grounded insights for teacher professional development - Haßler, Björn; Hennessy, Sara; Hofmann, Riikka (Journal of Learning for Development, 2018)
Developing sustainable and scalable educational initiatives is a key challenge in low-income countries where donor-funded short-term projects are limited by both contextual factors and programme design. In this concept paper we examine some of the issues related to in-service teacher development in the context of sub-Saharan Africa, grounded predominantly in our experiences of over 5 years of iteratively developing, refining and evaluating an intensive school-based professional learning programme for primary school teachers. “OER4Schools” integrates interactive pedagogy, Open Educational Resources (OER) and use of mobile devices (where available). The focus of this paper is on identifying what the main factors are perceived to be in sustaining and scaling up such a programme, from the perspectives of participating teachers, workshop facilitators and the research team. Synthesising our previous research and drawing on recent work in the field, we identify the key characteristics of effective and sustainable professional learning in low-resourced contexts. Such characteristics include effective peer facilitation, school-based active learning, explicit programme structure, appropriate scheduling and resourcing, and mitigating resource constraints through use of OER. Our conclusions thereby offer insights concerning the importance and impact of wider influences on participation and engagement of stakeholders and lead to recommendations for programme design and implementation, that should be taken on board by future initiatives.
Keywords: AWP2; Active Learning; Africa; Author:Haßler; C:sub-Saharan Africa; CitedIn:DFID_SRF; CitedIn:OER4S-TPE-Anon; CitedIn:OER4Schools-2012-HHH1-anon; CitedIn:PhD_Thesis; DIAL-RDO; Developing Nations; Educational Technology; Elementary Secondary Education; Faculty Development; Foreign Countries; Handheld Devices; IMPORT_FROM_DFID_RITE; InPrep; Inservice Teacher Education; Low Income Groups; Motivation; OER4Schools; Open Educational Resources; Peer Teaching; RPF-May-2016; Resource Allocation; Rural Schools; Scaffolding (Teaching Technique); Scheduling; Shared Resources and Services; Sustainable Development; Sustainable Development Goal 4; Teacher Professional Development; Technology Uses in Education; Telecommunications; ___working_potential_duplicate; dode_eth-src-dode; dode_eth-trf2-dode; missingHU; peer-facilitation; school-based active learning; sub-Saharan Africa; ⛔ No DOI found

Donor Organizations & the Principles for Digital Development: A Landscape Assessment and Gap Analysis. (Principles for Digital Development — Resource Development Program Asset No. 1) - Haßler, Björn; Brugha, Meaghan; Muyoya, Chisenga; Mitchell, Joel; Hollow, David; Jackson, Alan (Jigsaw and Open Develoment & Education, 2018)
Donor Organizations & the Principles for Digital Development: A Landscape Assessment and Gap Analysis. (Principles for Digital Development — Resource Development Program Asset No. 1)   Also available at https://digitalprinciples.org/resource/donor-organizations-the-principles-for-digital-development-a-landscape-assessment-and-gap-analysis/, https://digitalprinciples.org/wp-content/uploads/PDD2018_interactive.pdf
Keywords: _DOILIVE; _not_EdTechHub; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode

Synergies Between the Principles for Digital Development and Four Case Studies - Haßler, Björn; Broadbent, E.; Cunningham, A.; Chimombo, J.; Jamil, B. R.; Kauthria, R.; Lake, L.; Rose, P.; Sarfraz, S.; Szekely, M. (Research for Equitable Access and Learning (REAL) Centre, Faculty of Education, University of Cambridge, 2018)
This report was prepared by Bjöern Haßler for the Research for Equitable Access and Learning (REAL) Centre, University of Cambridge, UK, with support from the Global Education & Skills Forum (GESF) Alliance on Assessment and Impact for Learning. This Alliance was co-chaired by Pauline Rose (REAL Centre, University of Cambridge, United Kingdom) and Baela Raza Jamil (Idara-e-Taleem-o-Agahi, Pakistan) and included the following members: Emma Broadbent (The Varkey Foundation, United Kingdom), Andrew Cunningham (Aga Khan Foundation, Switzerland), Joseph Chimombo (Ministry of Education, Malawi), Rashmi Kauthria (Global Teacher Prize Finalist 2017, India), Lucy Lake (Camfed, United Kingdom), Shajia Sarfraz (Independent Researcher, Pakistan) and Miguel Szekely (Center for Education and Social Studies, Mexico).
Keywords: _DOILIVE; ___working_potential_duplicate; _not_EdTechHub; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode